Investigations of Zeolitic Materials at the NIST Center for Neutron Research - Toby, B. H. (J Res Natl Inst Stand Technol, 2001)
Crystallographic studies of four zeolitic materials using neutron powder diffraction data are presented. In most cases, these projects benefited from the combined use of neutron and x-ray measurements.